Cartografia e geopolítica das relações sul-sul: sobre a cooperação técnica Brasil-África. - André Santos da Rocha (Confins)
In last 20 years, Brazil sought alternatives to boost its projection in the world stage and one of these paths was the reorientation of its foreign policy which valued South-South relations. These relations are characterized by commercial ties, political alignment and technical cooperation agreements with peripheral and emerging countries. We understand the foreign policy and South-South cooperation as a form of geopolitical exercise of hegemonic projection and that the incentives to the cooperation agreements were part of a projection that would territorialize the global strategies of a State. Throughout 2003-2010, the Africa continent was the target of this Brazilian South-South foreign policy strategy, thus receiving great part of the technical cooperation investments. Therefore, we present a cartography of the main areas of the technical cooperation and demonstrate that, as a whole, it expresses a geopolitical trend that broadens diplomatic relations with other countries of African continent, beyond those already consolidated partners – the Portuguese-speaking countries.